An examination of selected public health exceptions in Asian patent laws - Kiyoshi Adachi (South Centre, 2022)
This study examines the variations within Asia of two exceptions to patent rights that are commonly justified under Article 30 of the World Trade Organization (WTO) Agreement on Trade-related Aspects of Intellectual Property Rights (the TRIPS Agreement), namely the research and experimentation exception and the regulatory review (or "Bolar") exception. Both these exceptions are important in the context of the 2001 Doha Declaration on the TRIPS Agreement and Public Health insofar as they are designed to provide flexibility to protect public health and support countries' overall scientific and technological aspirations. The study examines, from a comparative perspective, examples of these respective exceptions in patent legislation in South, Southeast and East Asia, and identifies peculiarities in the variations among countries in these sub-regions.
Keywords: 300; Access to Medicines; Article 30 TRIPS; Asia; Bolar; Doha Declaration on the TRIPS Agreement and Public Health; East Asia; Experimentation Exception; Flexibilities; Health; Intellectual Property; Patent; Public Health; Research Exception; South Asia; South East Asia; TRIPS; TRIPS Agreement